Predicting academic achievement of pre-service teachers based on critical thinking dispositions - Abdul Jalil, Amalina Ulya; Joari, Robi'atul 'Adawiyah; Nor Azman, Nur Adilah Aishah; Noor Mohamed Saleh, Norasaliza; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The aim of this research is to predict the significance between critical thinking disposition and academic achievement among pre-service teachers. The critical thinking disposition consists of seven elements of cognitive skills which are truth seeking, open mindedness, analyticity, systematicity, inquisitiveness, self-confidences and maturity as indicated by the Critical Thinking Disposition Inventory (CTDI). Data was analysed using IBM Statistics to gather descriptive data and analyse the inferential data through ANOVA. Further analyses are expected to show that there will be a relationship between each elements of critical thinking disposition and academic achievement of pre-service teachers. Based on review of past studies, it is expected that the ANOVA outcome will be significant for the seven elements of cognitive skills of thinking disposition. It is also be presumable that high critical thinking disposition among pre-service teachers could enhance their academic achievement.